(untitled) (Journal of Technology and Operations Management, 2017)
The purposes of this research are: 1) to study problems of the batik business in Narathiwat province and 2) To study the capabilities of development needs of the batik business in Narathiwat province. Samples in this study are seven groups of the owners of the batik businesses in Narathiwat province with 4 and 5 star national assessments. Data were collected through a series of questionnaire-based interview forms and Data were analyzed with statistical percentage basic. The results showed that the majority of Entrepreneurs batik were females ages 41 to 50 of high school graduation, earning monthly salary of 5,001-30,000 baht. A period of implementation of the batik business was 5-10 years. The number of the batik workers were over 20 people. Twenty one and four owners expanded their businesses in domestic and international markets, respectively. The operational problems of the batik business were insufficient funds, market behavior with demand uncertainty, a lack of advertising and public relations, insufficient knowledge of entering a new market, high rates of production losses, high employee turnover, inconstant government support and insufficient government public relations efforts. Business development capability requirements were financial and marketing skills training program, promotional marketing, internal and external markets, raw materials, knowledge providers, modern information services, public relations, and export promotion.